Factors Affecting Breastfeeding during 6 months to 2 Years of Adolescent at Police General Hospital - Keskomon, Thipkhumporn; Pansang, Kandamanee; Poungjuntaradej, Naowanit; Klinsukon, Chutikan; Boonleart, Dawsakun; Thongkam, Pawadee; Sommai , Sajeewit; Roon-aoy , Saowaluck; Ketsingnoi, Theerapong (Journal of The Royal Thai Army Nurses, 2023)
The objective of this research was to study the causal relationship of spouse’s support in raising children, good attitude towards child, positive attitude towards breastfeeding, and love support breastfeeding behaviors during 6 months to 2 years of 71 adolescent mothers who received services at the Police General Hospital. The instruments consisted of a 6-level evaluation measure of spouse’s support in raising children, good attitude towards child, positive attitude towards breastfeeding, and love support breastfeeding behaviors, 10 items for each. The content validity was equal to 1.0. Cronbach’s alpha coefficients were .73, .75, .77 and .78, respectively. Data were analyzed using frequency, percentage, arithmetic mean, standard deviation, correlation coefficients, and multiple regression analysis. The results showed that spouse’s support in raising children, good attitude towards child, positive attitude towards breastfeeding, and love support breastfeeding behaviors during 6 months to 2 years of adolescent mothers were related to each other at the .001 level (r = .282 - .689). These variables were not related to the duration of raising children with breastfeeding. Good attitude towards children and a positive attitude towards breastfeeding could jointly explain the variation in supportive breastfeeding behaviors of adolescent mothers (43.0 %). Professionals should promote the role of spouses in supporting child rearing all stages of pregnancy and the role in breastfeeding support of family and society.